A review of research trends on meta-cognitive in science education within the past decade. Issue 1 (March 2021) - Rusyati, L; Rustaman, N Y; Widodo, A; Ha, M
Abstract: Metacognition and its implications for learning and instruction have become a central issue in educational research. The objective of the current review is mapping the field of meta-cognitive research trends in science education within the past decade. Furthermore, this study build the state of the art on meta-cognitive and describe the possibility research in the future. This study as a baseline for further research which focus on meta-cognitive integrated with other skills. The survey was implemented as method for this research. The major purpose of surveys is to describe the characteristics of a population. The subject for this study is 30 articles which is focusing on meta-cognitive in science education and have highest citation within the past decade (year 2009-2019). The articles come out from databases 'Google scholar' and from reputable journals. Form of coding scheme is main instrument for this study. The finding describes that Research trends on meta-cognitive in science education dominant conducted in higher education for pre-service teachers. Furthermore, for metacognitive aspects generally focus on aspect Metacognitive Skills (MS) sub aspect regulating/controlling and Metacognitive Knowledge (MK) about strategies for science concepts in domain-general. Meanwhile, based on role, research on meta-cognitive focus as the input. The implication of research trends on meta-cognitive provide opportunities for conducting research in lower education for discipline-specific science. The further research also can assess on Metacognitive Experiences (ME) and Metacognitive Skills for sub aspect monitoring, evaluating and planning.